Endoscopic retrieval of migrated gastric band - Chirinos-Vega, Juan Antonio (2023)
This is a case report of a 47-year-old woman, carrier of an adjustable gastric band since 2018, that developed abdominal pain due to partial migration into the stomach. which was successfully removed endoscopically using Sohendra's lithotriptor.